Developing a Plume‐in‐Grid Model for Plume Evolution in the Stratosphere. (28th March 2022) - Sun, Hongwei; Eastham, Sebastian; Keith, David
Abstract: Stratospheric emissions from aircraft or rockets are important sources of chemical perturbations. Small‐radius high‐aspect‐ratio plumes from stratospheric emissions are smaller than global Eulerian models' grid cells. To help global Eulerian models resolve subgrid plumes in the stratosphere, a Lagrangian plume model, comprising a Lagrangian trajectory model and an adaptive‐grid plume model with a sequence of plume cross‐section representations (from a highly resolved 2‐D grid to a simplified 1‐D grid based on a tradeoff between the accuracy and computational cost), is created and embedded into a global Eulerian (i.e., GEOS‐Chem) model to establish a multiscale Plume‐in‐Grid (PiG) model. We compare this PiG model to the GEOS‐Chem model based on a 1‐month simulation of continuous inert tracer emissions by aircraft in the stratosphere. In the PiG results, the final injected tracer is more concentrated and approximately 1/3 of the tracer is at concentrations 2–4 orders of magnitude larger compared to the GEOS‐Chem results. The entropy of injected tracer in the PiG results is 6% lower than the GEOS‐Chem results, indicating less tracer mixing. The total product mass from a hypothetical second‐order process (applied to the injected tracer) in the PiG results is 2 orders of magnitude larger than the GEOS‐Chem results. Increasing the GEOS‐Chem model's horizontal resolution 4‐fold is insufficient to resolve this product difference, while requiring over seven times the computational resources of the PiG model. This paper describes the PiG model framework and parameterization of plume physical processes. Chemical and aerosol processes will be introduced in the future. Plain Language Summary: Computer models used to understand how aircraft damage the environment usually split the atmosphere into large boxes with a length scale of ∼100 km, ignoring smaller scale variations in pollutants inside the box. Pollution produced by aircraft is released in narrow plumes that are much smaller than the box. Some chemical or physical processes could occur much faster inside a high‐concentration exhaust plume than when the same amount of pollution is spread out over the large box, which may produce big errors in calculating the impact of aircraft emissions in the stratosphere where plumes mix slowly. This also causes problems for predicting the impacts of solar geoengineering in which aircraft emit reflective material to cool the planet. One can fix the problem by making the boxes much smaller, which requires too much computer time to be practical. We describe a method using smaller boxes just where they are most needed at the plume. After the plume has spread a bit, our "plume‐in‐grid" model then eliminates the small boxes and gives the information back to the conventional computer model's big box. This can allow more accurate calculations of the impacts of pollution plumes for a given amount of computing time. Key Points: A Lagrangian plume model is created and embedded into a global Eulerian model to establish a Plume‐in‐Grid (PiG) model The PiG and global Eulerian models are compared by a 1‐month simulation of continuous stratospheric emissions from an aircraft The PiG model resolves nonlinear plume‐scale processes at a fraction of the computational cost of fine‐resolution global Eulerian models